The cultural impact of selected television advertisements within an African community - Neluvhalani, Kanelani Elsie (My University, 2001)
Refer to the document
Thesis (M.A. (African Languages)) -- University of the North, 2001
Keywords: Television advertisements; Cultural values; African community; Television commercials; Advertising; Television advertising